α-Selective Glycosylation of 3,6-O-o-Xylylene-Bridged Glucosyl Fluoride - Motoyama, Atsushi; Arai, Tomoki; Ikeuchi, Kazutada; Aki, Kazuya; Wakamori, Shinnosuke; Yamada, Hidetoshi (Synthesis, 2018)
A 1,2-cis-(α)-selective glycosylation has been developed. An ortho-xylylene group bridged between 3-O and 6-O of d-glucosyl fluoride, which straddles the β-face of the pyranose ring, hinders the approach of glycosyl acceptors from that face. The determination of the three-dimensional structure of the bridged glucosyl fluoride, the optimization process of the reaction conditions oriented toward kinetic control to realize the high α-selectivity, and the scope of the reaction are described.
Keywords: glycosylation; 1,2-cis-selectivity; kinetic control; conformation; o-xylylene bridge